A New Chapter in the Management of Hypertrophic Cardiomyopathy Cardiac Myosin Inhibitors - Pálinkás Eszter Dalma (CARDIOLOGIA HUNGARICA, 2023)
In the recent years, there has been a significant breakthrough in the treatment of hypertrophic cardiomyopathy. New precision molecules have been developed and successfully applied in clinical trials. A new class of orally available allosteric inhibitors reduces heart muscle hypercontractility, the core molecular defect of the disease, by selectively inhibiting cardiac beta-myosin. Based on the results obtained with the first two agents developed to date, mavacamten and aficamten, their use is safe and is associated with rapid and unprecedented improvement in quality of life and functional capacity in patients with left ventricular outflow tract obstruction, comparable to an optimal surgical result. This review provides an overview of the latest and most important studies that led to the approval of mavacamten by the U.S. Food and Drug Administration, and the clinical development of aficamten.